Application of the Capabilities, Opportunities, Motivations, and Behavior (COM-B) Change Model to Formative Research for Child Nutrition in Western Kenya. Issue 7 (21st June 2022) - McClintic, Emilie Ewart; Ellis, Anna; Ogutu, Emily A; Caruso, Bethany A; Ventura, Sandra Gomez; Arriola, Kimberly R Jacob; Kowalski, Alysse J; Linabarger, Molly; Wodnik, Breanna K; Muga, Richard; Freeman, Matthew C; Girard, Amy Webb
ABSTRACT: Background: Interventions aimed at improving dietary intake and feeding practices have alone proven insufficient for combatting stunting resulting from poor nutrition and repeated infections. Objectives: To support the development of an integrated water, sanitation, and hygiene (WASH) and nutrition, social, and behavior change strategy aimed at reducing stunting, formative research was conducted in 2 program sites in western Kenya. Methods: Twenty-nine key informant interviews were conducted with community leaders, health workers, and project staff, and 24 focus group discussions with caregivers of children under 2 y on topics related to feeding, sanitation, and hygiene behaviors. Three frameworks informed the study design and analysis of our formative research: the Capabilities, Opportunities, and Motivations model for behavior change, which identifies what needs to change in order for behavior change interventions to be effective; the Grandmother Project's Change Through Culture Approach, which values the important role of influential household and community members in producing household health; and Starr and Fornoff's approach to Theory of Change development. Results: Caregivers exhibited sufficient psychological capabilities (knowledge and skills) for many of the key maternal and infant nutrition behaviors. However, reflective motivation to perform optimal behaviors was undermined by limitations in physical and social opportunities, including limited time and competing priorities for mothers, limited accessibility and availability of diverse foods, low self-efficacy for exclusive breastfeeding, and fears of negative consequences related to specific foods and recommended practices. Conclusions: Interventions that aim to improve maternal and child diets should address the underlying social, cultural, and environmental determinants that contribute to motivations and opportunities to perform recommended practices. Abstract : Nutrition-sensitive strategies that address capability, opportunity, and motivation may have further reaching impacts on maternal and child diets compared with traditional nutrition-specific approaches.